Evaluating the Undrained Shear Strength of Kalimati Soil Using Field Vane and Unconfined Compression Test; a Study on Applicability of Bjerrum’s Correction Factor - Pandey, Sanjaya; Lamichhane, Anup; Acharya, Indra Prasad (Journal of Advanced College of Engineering and Management, 2023)
Rapid urbanization and geological challenges in Kathmandu have made it crucial to understand the geotechnical properties of the soil in the region. This study here focuses on the undrained shear strength of silty clay in Kalimati, Kathmandu, and investigates the applicability of Vane Shear tests and its parameters over other shear strength tests from other methods. Geotechnical investigations were carried out at three locations within the Kathmandu Engineering College premises and in-situ and laboratory tests were conducted on undisturbed and disturbed samples. Then the study compared the field vane shear strength, undrained strength from unconfined compression tests, and laboratory vane shear strength of the samples. For the field vane shear test the correction factor as suggested by Bjerrum was used and the results indicate that this method overestimates the shear strength in Kalimati soil, indicating no adjustment is necessary. The findings of this study have important implications for the design and construction of structures in the region, and contribute to a better understanding of the geotechnical properties of Kathmandu soil.